Morphological effect of dispersed phase on gas permeation properties through heterophase polymer membrane: theoretical and experimental approaches - Park, C; Jo, WH; Park, HC; Kang, YS (ELSEVIER SCI LTD, 2000)
The possibility of the continuous channel formation of the dispersed phase in immiscible polymer blends was numerically simulated by adopting the percolation concept. The numerical simulation showed that the formation probability of the continuous channels increased with the increase in the amount of the dispersed phase. Further, it increased with the decrease in the domain size of the dispersed phase at a given blend composition. The effect of the presence of the continuous channels of the dispersed phase across the membranes on gas transport properties was investigated experimentally. The domain size of the dispersed polyisoprene phase of poly(phenylene oxide)/polyisoprene (PPO/PI) blend membranes was controlled by adding the styrene-isoprene-styrene (SIS) block copolymer. When the SIS block copolymer was added at 4 wt% in PPO/PI membranes in the range of the PI content of 20-30 wt%, the domain size of the dispersed phase was reduced markedly and its permeability was consequently increased. From the theoretical and experimental results, it could be concluded that the abrupt increase in gas permeability of the blend membranes at 20-30 wt% of PI phase may result from the formation of the continuous channels of the more permeable dispersed phase when the block copolymer is added. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: POLY(1-TRIMETHYLSILYL-1-PROPYNE) PTMSP; POLY(1-PHENYL-1-PROPYNE) PPP; BLEND MEMBRANES; CARBON-DIOXIDE; PERMEABILITY; TRANSPORT; SORPTION